Us - Peele, Jordan 1979- (Inventory Press, 2024)
"Published in conjunction with the fifth anniversary of the critically acclaimed film's release, this companion paperback features Oscar-winning director Jordan Peele's screenplay, alternate endings and deleted scenes, and is richly illustrated with over 150 stills from the motion picture. Specially commissioned annotations by hannah baer, Theaster Gates, Jamieson Webster, Jared Sexton, Mary Ping, Shana Redmond and Leila Taylor present a cosmology of images, definitions and inspirations that extend the themes of the film."--Publisher's description
Keywords: Peele, Jordan -- 1979-; Us (Motion picture); Doppelgängers / Drama; Survival / Drama; PERFORMING ARTS / Screenplays; Drama; Théâtre; Drehbuch